Foreign language learning and job opportunity for learners - Nguyễn Thị Việt Phương (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In today’s era of globalization, foreign language has become a must-have tool for anyone who wants a good job opportunity. Learning foreign languages ​​has become a trend for any young person. Simply because the mother tongue, you may lose the opportunity to work in multinational companies and reduce the ability to compete directly with other candidates who are fluent in foreign languages. The article gives some views as well as suggestions on learning foreign languages ​​in the current period.